Urban spatial change and excess commuting - Ma, K; Banister, D (Pion, 2007)
In this paper we revisit the excess-commuting technique and its links with urban form. The uncertainty in measurement is highlighted, as are the problems relating to changes in excess commuting over time. The measure of the theoretical maximum commute is proposed and added to the traditional excess-commuting measure so that the use of both the minimum and maximum levels can capture the concept of commuting potential. This measure is what we call the ‘extended excess-commuting measure’. These concepts are tested through the use of a simulation exercise. As well as arguing for the inclusion of socioeconomic variables in analysis, we demonstrate that decentralisation in urban spatial structure can lead to either an increase or a decrease in average commuting distance. Some of the inconsistencies in the use of excess commuting can be reduced through the use of actual commutes together with the commuting range, as these factors in combination lead to a clearer understanding of commuting efficiency.